Oncological Safety of Diagnostic Hysteroscopy for Apparent Early-Stage Type II Endometrial Cancer: A Multicenter Retrospective Cohort Study - Zhou, Hui; Lai, Kai-Fa; Xiang, Qian; Xu, Yu; Zhang, Qian-Wen; Hu, Cui; Mao, Xi-Guang; Chen, Cheng; Huang, Wu; Mi, Gong-Sheng; Shen, Juan; Tian, Yong; et al. (Frontiers in Oncology, 2022)
Objective To compare the impact of methods of endometrial sampling on the prognosis of apparent early-stage type Ⅱ endometrial cancer. Patients and Methods A total of 429 women with presumed early-stage type Ⅱ endometrial cancer were included. The 5-year DFS and OS were estimated and compared using the Kaplan-Meier method and the log-rank test among patients diagnosed by Dilation & Curettage (D&C) or diagnostic hysteroscopy. The Cox proportional hazards regression model was employed to adjust for potential confounding factors. Results 160 cases underwent D&C and 269 cases diagnosed by diagnostic hysteroscopy. The 5-year DFS rate was 72.17% in the hysteroscopy group and 76.16% in the D&C group, diagnostic hysteroscopy was not associated with deteriorated 5-year DFS (HR 1.25, 95% CI 0.84-1.86, P=0.281). The 5-year OS rate was 67.23% in the hysteroscopy group and 70.71% in the D&C group, diagnostic hysteroscopy did not increase the risk of all-cause death (HR 1.11, 95% CI 0.78-1.57, P=0.573). Multivariable analysis showed that the method of endometrial sampling was not independently associated with DFS (aHR 1.38, 95% CI 0.92-2.07, P=0.122) and OS (aHR 1.23, 95% CI 0.85-1.77, P=0.272). Conclusion For apparent early-stage type Ⅱ endometrial cancer, diagnostic hysteroscopy did not affect the oncological outcomes.